(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this work, the thermal efficiency of a dual-operated solar cooking and drying system that may be utilized for domestic use was examined. An analysis of the system’s thermal performance was conducted at Sokoto Energy Research Centre (SERC) using the Bureau of Indian Standards (BIS). Sampling cooking and drying tests were carried out, and the potential for extended cooking time for brine solution and animal fat was conducted. The results showed that the first figure of merit (F1) value agrees with the standard value of 0.12 and the second figure of merit (F2) value is in close correspondence with 0.25 (BIS Standard). The system was able to dehydrate 89 % of the moisture content of banana slices weighing 118 g which is of uniform thickness of 4 mm to achieve a stable weight of 12 g after 8 hours of drying. Animal fat showed more potential for extended cooking time than brine solution, as it took 5 hours to cool after heating for about 3 hours. Six pieces of eggs were boiled for 45 minutes in a temperature range of 29.7 oC and 88.2 oC. These findings indicate the potential of this dual-operated system for domestic applications.